If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 = 9x + -5 Reorder the terms: 40 = -5 + 9x Solving 40 = -5 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 40 + -9x = -5 + 9x + -9x Combine like terms: 9x + -9x = 0 40 + -9x = -5 + 0 40 + -9x = -5 Add '-40' to each side of the equation. 40 + -40 + -9x = -5 + -40 Combine like terms: 40 + -40 = 0 0 + -9x = -5 + -40 -9x = -5 + -40 Combine like terms: -5 + -40 = -45 -9x = -45 Divide each side by '-9'. x = 5 Simplifying x = 5
| 10-2lnx=7 | | 5(x-3)6=5x-10 | | (-3y^2+2y+1)= | | 4x-(5-7X)-6=11 | | .18(18)+.02x=.06(6+x) | | -6x+3=-51 | | 1.4+0.2x=0.5x-3.4 | | 9=9+5x | | (2+i)+(-3+9i)= | | (5y^2-7y+6)= | | 4(2x-2)=6(3x+2) | | h=-0.2d^2+2.2d+12 | | 7x+9x+11=180 | | log(x-2)=log(3x+7) | | 16x+95=170 | | -45-1x=30-6x | | p^2+7p-1=7 | | 5(9x-11)=485 | | t^2+4t+5=0 | | 10y-40=3y+9 | | -10y+7=37 | | 3-8x=-125 | | 2x(4x+x)=16 | | 9(9x-16)=585 | | -32-8k=-(5+k) | | g(x)=4x+5 | | 0=8+7*cos(3*t)+7*cos(6*t) | | 26x+51y= | | 15=1.3 | | 5x+14=99 | | x(x-28)= | | x(x-6)+5=0 |